Test methods for electrical materials, printed boards and other interconnection structures and assemblies. General test methods for materials and assemblies. Reflow soldering ability test for solder joint, and reflow heat resistance test for printed boards Part 5-601, (19th March 2021) - British Standards Institution,
No abstract available